Computer usage, destination language proficiency and the earnings of natives and immigrants - Chiswick, B.; Miller, Paul (Springer New York LLC, 2007)
This paper uses the concept of a computer as a public good within the household to model the demand for computers at home. It also investigates the determinants, and consequences for earnings, of computer use. The equations are estimated using data on the native born and immigrants from the 2001 Census of Population and Housing in Australia. The multivariate analyses show that recent arrivals are more likely to use computers than the Australian born. The data suggests a high degree of favorable selection in migration as the level of computer use in Australia is much higher than in most of the countries that Australia’s immigrants come from. Those with a higher permanent income (education, household assets) are more likely to have a computer at home, but there is no effect of transitory income (unemployment). Immigrants who are more proficient in English are also more likely to use a computer. The relation between age and computer use is strongly influenced by cohort effects. Using a computer at home is associated with about 7% and 13% higher earnings for native-born and foreign-born men, respectively. For the immigrants, the effects of schooling and English language proficiency on earnings are greater among those who use a computer at home. This suggests complementarity in the labor market. The use of a computer is shown to be a way the foreign born can increase the international transferability of their pre-immigration skills, a finding that has implications for immigrant assimilation policies.